Effects of levodopa alone and in combination with dopa-decarboxylase inhibitors on plasma renin activity in patients with Parkinson's disease. Issue 10 (October 1978) - Rappelli, A; Glorioso, N; Tedde, R; Dessi'-Fulgheri, P; Monaco, F
Abstract : Plasma renin activity (PRA) of patients with Parkinson's disease was measured in recumbency, upright position, and after frusemide administration. The results show that the renin responses to both stimuli are significantly reduced as compared with those obtained in a group of normal subjects, while recumbent PRA levels of Parkinsonism patients are not significantly lower than those found in recumbent normal subjects. Levodopa treatment, alone or in combination with two different dopa-decarboxylase inhibitors, benserazide and carbidopa, does not modify the renin response to posture or to frusemide. Although the reduced activity of the renin-angiotensin system can play some role in the genesis of orthostatic hypotensive episodes encountered in patients with Parkinsonism, the greater incidence of orthostatis hypotension in patients treated with levodopa seems to be unrelated to any effect of this drug on the renin release.